La pensée colorblind à l’épreuve du ghetto : retour réflexif sur un terrain étatsunien - Yohann LE MOIGNE (E-REA)
This article is a reflexive analysis of the epistemological and theoretical in-between that was the main fieldwork conducted during my doctorate in geography, which dealt with power rivalries between African-Americans and Latinos in the city of Compton (California).It aims at highlighting the dialectical relationship between this fieldwork and the late discovery of theoretical works on race and racism which opened my eyes on the way the social, disciplinary and scholastic biases identified by Pierre Bourdieu had hindered my initial understanding of the conflicts analyzed in the field.